A greener electrochromic liquid crystal based on ionic liquid electrolytes. Issue 8 (20th June 2016) - He, Zemin; Yuan, Xiao; Zhao, Yuzhen; Zou, Cheng; Guo, Shumeng; He, Baofeng; Zhang, Haiquan; Zhang, Lanying; Yang, Dengke; Yang, Huai
ABSTRACT: An electrochromic liquid crystal (ECLC) material composed of only liquid crystal (LC) and ionic liquid (IL) was developed. The LC containing the substituted diphenylacetylene serves as electrochromic (EC) material to realise transmittance and colour change under the direct current (DC) field, while the IL with the designable cation and anion served as electrolyte. Herein, a series of IL electrolytes was screened to investigate how IL tunes the electro-optic performance of the ECLC cell. By testing the electrochemistry window of ILs in EC cells, IL with the [NTf2 ] − anion shows adequate electrochemical stability when the EC material undergoes oxidation and reduction. The electro-optic performance of ECLC containing 1-ethoxy-4-[2-(4-pentylphenyl) ethynyl]-benzene (PEB) and IL was then evaluated by UV-vis spectrometry under the control of an electrochemical work station. Compared with other PEB-IL, PEB-[Bmim][NTf2 ] with [Bmim][NTf2 ] electrolyte shows a satisfactory transmittance at low operating voltage. Furthermore, Pd NPs in situ formed in [Bmim][NTf2 ] reduced the EC potential and improved the light scattering of the ECLC cell. In this work, we also designed a bifunctional device based on polymer dispersed liquid crystal (PDLC) that hosts electrochromic guest molecules, and analysed the electro-optical and electrochromic properties of LC electrolyte mixtures, in order to gain control of the incident daylight and glare in building and automotive applications. GRAPHICAL ABSTRACT: